Improving Students' Comprehension about Energy Sources through Sparkol Videoscribe-Based Learning Media - I Made Agus Pranata; I Nyoman Laba Jayanta (Jurnal Ilmiah Sekolah Dasar, 2021)
There were still many teachers who had not been able to create a pleasant learning atmosphere for students. In addition, the lack of learning media made it difficult for students to understand the subject matter. This study aimed to develop learning media based on sparkol video scribe to facilitate students in learning. The type of this research was development research and used the ADDIE model. Subjects in this study amounted to 5 people. The methods used in collecting data were observation, interviews, and questionnaires. The instrument used in collecting data was a questionnaire. The data analysis technique used in this development research was using qualitative descriptive statistical analysis techniques and quantitative descriptive statistics. The study results showed that the expert test of the subjects developed got a very good category, learning design experts got a very good category, test results from learning media experts got a very good category. The results of individual trials got very good qualifications. It can be concluded that the media developed was feasible to be applied in learning. This research implies that the developed media can make it easier for students to understand science subject matter.